The Developed Relations between Social Class and Language in United Kingdom and United State of America - Laily Lainiyah; Tadkiroatun Musfiro (Yayasan Visi Intan Permata, 2020)
There has been an arising issue related to the correlation between language and social among social communities in United Kingdom and America. Both of the social communities usually employ different language varieties which are in accordance to the position of social class. In England, the higher social community tends to use Received Pronunciation while the lower social community tends to use estuary accent. On the other hand, in America, the higher social community tends to use Standard English while the lower social community tends to use African American English. The present study primarily focuses on the relationship between language and social class in United Kingdom and America in which the association of the language and social class is described qualitatively through reviewing any literatures related to the aforementioned issue. After examining the data, it is showed that, nowadays, even though Received Pronunciation is considered as the standard English in United Kingdom, the speakers of the language are only 3%. Furthermore, the Estuary accent is now used by the broadcasting station even though in the past they only used the Received Pronunciation. In addition, African American Language, which is considered as the language of lower social class, in the present day is also used by white people as upper class in America